A Study on the Fluorescence Properties of New Laser Material-n-B18H22 in SDS Aqueous Solution - Lin-Na Zhang; Jie Chen; Xu-Guang Huang; Hong-Yun Meng; Chun-Hua Tan (International Journal of Optics)
The effect of anionic surfactant sodium dodecyl sulfate (SDS) on the fluorescence of n-B18H22 was studied. The experimental result revealed that the fluorescence of n-B18H22 was obviously enhanced with the increase of the concentration of SDS, mainly due to the hydrophobic protection of n-B18H22 by SDS. Under the optimum conditions, the fluorescence intensity was proportional to the concentration of n-B18H22 in the range of 0-8.0×10−3 mol·L−1 and 8.0×10−3 mol·L−1-3.3×10−2 mol·L−1, respectively. It was observed that a break appeared in the curve of fluorescence intensity with surfactant concentration. The critical micelle concentration (CMC, 7.9×10−3 mol·L−1) of SDS was obtained from this break point in a good agreement with the reported value. The fluorescence intensity increased initially with time and gradually stabilized. The results form the basis for further study of the properties and application of n-B18H22 in SDS solutions.